Strategic appraisal : the changing role of information in warfare - Khalilzad, Zalmay; White, John Patrick, 1937-; United States. Air Force; Rand Corporation; Project Air Force (U.S.) (Santa Monica, CA : RAND, 1999)
Advances in information technology have led us to rely on easy communication and readily available information--both in our personal lives and in the life of our nation. For the most part, we have rightly welcomed these changes. But information that is readily available is available to friend and foe alike; a system that relies on communication can become useless if its ability to communicate is interfered with or destroyed. Because this reliance is so general, attacks on the information infrastructure can have widespread effects, both for the military and for society. And such attacks can come from a variety of sources, some difficult or impossible to identify. This, the third volume in the Strategic Appraisal series, draws on the expertise of researchers from across RAND to explore the opportunities and vulnerabilities inherent in the increasing reliance on information technology, looking both at its usefulness to the warrior and the need to protect its usefulness for everyone. The Strategic Appraisal series is intended to review, for a broad audience, issues bearing on national security and defense planning.
Introduction / Zalmay Khalilzad and John White -- The American military enterprise in the information age / Carl H. Builder -- Right makes might : freedom and power in the information age / David C. Gompert -- Networks, netwar, and information-age terrorism / John Arquilla, David Ronfeldt, and Michelle Zanini -- Information and war : is it a revolution? / Jeremy Shapiro -- Information and warfare : new opportunities for U.S. military forces / Edward Harshberger and David Ochmanek -- U.S. military opportunities : information-warfare concepts of operation / Brian Nichiporuk -- The information revolution and psychological effects / Stephen T. Hosmer -- U.S. strategic vulnerabilities : threats against society / Roger C. Molander, Peter A. Wilson, and Robert H. Anderson -- Implications of information vulnerabilities for military operations / Glenn C. Buchan -- Military organization in the information age : lessons from the world of business / Francis Fukuyama and Abram N. Shulsky -- Arms control, export regimes, and multilateral cooperation / Lynn E. Davis -- Ethics and information warfare / John Arquilla -- Defense in a weird world : protection, deterrence, and prevention / Zalmay Khalilzad -- Conclusion : The changing role of information in warfare / Martin Libicki and Jeremy Shapiro.
"Prepared for the United States Air Force."
"Rand."
"Project AIR FORCE."
Includes bibliographical references.
Print version record.
English.
Keywords: Military art and science -- Automation; Art et science militaires -- Automatisation; HISTORY -- Military -- Biological & Chemical Warfare; POLITICAL SCIENCE -- Security (National & International); Military art and science -- Automation